Community Empowerment to Strengthen Women’s Role in Food Security: Yard Optimization by the Aisyiyah Women Farmers Group in Sei Rotan Village, Deli Serdang, North Sumatra - Harahap, Rahma Hayati; Saladin, Teuku Ilham; Sudarwati, Lina (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2025)
Women’s involvement has been essential in supporting household food security and zero hunger sustainable development. Within families, women often play a crucial role in ensuring that all members receive safe and nutritious food. The Aisyiyah Women Farmers Group (Kelompok Wanita Tani, KWT) in Sei Rotan Village empowered women to engage in small-scale agriculture by utilizing their household yards. This community empowerment program aimed to improve the knowledge, skills, and independence of KWT members in optimizing yard spaces to strengthen women’s roles in achieving food security and promoting household food self-sufficiency. The program primarily targeted housewives who were active members of the KWT Aisyiyah. It was implemented through a combination of counseling, training, and mentoring using the Participatory Rural Appraisal (PRA) method. PRA facilitated the active participation of community members, enabling women to take on more prominent roles within both their families and the broader community. The program’s success was evaluated based on how effectively participants utilized their yards for agricultural purposes to meet their families’ nutritional needs. The crops grown by KWT members significantly reduced reliance on external sources of vegetables and contributed to sustaining healthy dietary practices within their households.